Selective effect of lithium on cognitive performance in man. - Glue, P; Nutt, D; Cowen, P; Broadbent, D (1987)
The effects of lithium on psychomotor performance were examined in six healthy male volunteers (aged 26-31 years) and compared with those of a similar control population. Three computerised psychomotor tests (serial reaction time, semantic reasoning and syntatic reasoning) were administered before lithium, after 5 and 22 days of lithium carbonate (800 mg/d) and 4 days and 1 month after stopping the lithium. The only significant effect was an impairment of semantic reasoning during the chronic (22 day) test. This suggests a selective effect of lithium on associative mental tasks and may explain the subjects' experience of slowing in recall of object names whilst taking lithium.